Association between the Infant and Child Feeding Index at 8 months and early childhood neurodevelopment - Li, Xiuxiu; Zhang, Jianan; Dai, Xiaowei; Liu, Xuemei; Gao, Rui; Liu, Xuhua; Wei, Min; Cai, Li (Frontiers in Nutrition, 2026)
ObjectiveTo evaluate the association between infant feeding practices, measured by the Infant and Child Feeding Index (ICFI) at 8 months, and early childhood neurodevelopment.MethodsA total of 705 participants were enrolled from the Shenzhen Birth Cohort Study (SZBC), a prospective longitudinal study. Infant feeding practices at 8 months were assessed via a validated dietary recall method combining 24 h and 7 day recall records. ICFI scores were calculated based on seven components (including breastfeeding and complementary feeding) and dichotomized into qualified (>60% of the total score) versus unqualified groups. Neurodevelopment was evaluated across five domains using the Ages and Stages Questionnaire, Third Edition (ASQ-3) at 8, 12, 18, and 24 months. Multivariable Generalized Estimating Equations (GEE) analyzed the association between ICFI status at 8 months and neurodevelopmental delay across early childhood.ResultsAt 8 months, 48.5% of infants had qualified ICFI scores. Across the five ASQ-3 domains, the prevalence of developmental delay between 8 and 24 months ranged from 1.0 to 16.8%. After controlling for confounders, infants in the qualified ICFI group exhibited significantly lower odds of delay in the communication domain (OR = 0.51; 95% CI: 0.35–0.75), the problem-solving domain (OR = 0.55; 95% CI: 0.32–0.95), and the personal-social domain (OR = 0.54; 95% CI: 0.37–0.79).ConclusionHigher ICFI scores at 8 months, indicating healthier feeding practices, are associated with reduced risk of neurodevelopmental delays through age two. These findings underscore the importance of promoting targeted feeding guidelines to support early childhood development.